Bidirectional substance P signaling between periodontal ligament fibroblasts and sensory neurons under mechanical stress - Symmank, Judit; Löffler, Lara; Schulze-Späte, Ulrike; Jacobs, Collin (Frontiers in Molecular Neuroscience, 2025)
IntroductionOrthodontic tooth movement (OTM) and treatment-associated pain are closely related processes driven by a local inflammatory response modulated by periodontal ligament fibroblasts (PdLFs). Increased levels of substance P (SP), a well-characterized tachykinin, has been demonstrated in the PdL following the application of orthodontic forces. Although traditionally considered as neurotransmitter modulating inflammatory processes and pain, recent evidence suggests that also non-neuronal cells contribute to SP signaling during OTM. Since sensory neurons also express the corresponding receptor NK1R, activation by SP appears to be possible. However, the contribution of PdLFs to SP signaling upon mechanical stress and their subsequent interaction with sensory neurons remain largely unexplored. Thus, the aim of the study was to investigate a potential SP-mediated interactions between PdLFs and sensory neurons advancing our understanding of molecular mechanisms underlying orthodontic pain during OTM.MethodsTAC1 and SP levels were quantified via qRT-PCR, Western blot, and ELISA in compressed human PdLFs. Their conditioned medium was applied to sensory-like SH-SY5Y neurons and their activation was assessed by morphological features, cFOS expression, and calcium influx. Conversely, PdLFs were stimulated with conditioned medium from capsaicin-activated SH-SY5Y neurons. Subsequently, cytokine expression, RANKL/OPG ratio and activation of immune cells and osteoclasts by PdLFs were evaluated.ResultsCompressive force induced a time- and intensity-dependent increase in TAC1 expression and SP secretion by compressed PdLFs with a peak at 24 h. Stressed PdLFs significantly increased neurite complexity, cFOS levels and calcium influx in sensory neurons, indicating their activation. Conversely, activated neurons elicited a robust pro-inflammatory response in PdLFs along with an increased osteoclastogenesis.DiscussionOur findings demonstrate that PdL fibroblasts could function as a novel non-neuronal source of SP modulating sensory neuron activation. Conversely, fibroblasts were also stimulated by SP effecting inflammation and osteoclastogenesis. These findings underscore a dynamic role of PdLF- and sensory neuron-derived SP that likely contributes to both pain perception and inflammatory bone remodeling during OTM.